EXPERIMENTAL CONSTRAINTS ON CRYSTALLIZATION DIFFERENTIATION IN A DEEP MAGMA OCEAN - Walter M.J.; Nakamura E.; Tr?nnes R.G.; Frost D.J. (My University, 2004)
Major and trace element mineral/melt partition coefficients are presented for phases on the liquidus of fertile peridotite at 23–23.5 GPa and 2300 °C. Partitioning models, based on lattice-strain theory, are developed for cations in the ‘8-fold’ sites of majorite and Mg-perovskite. Composition-dependant partitioning models are made for cations in the 12-fold site of Ca-perovskite based on previously published data. Dmin/melt is extremely variable for many elements in Ca-perovskite and highly correlated with certain melt compositional parameters (e.g. CaO and Al2O3 contents). The 8-fold sites in Mg-perovskite and majorite generally have ideal site radii between 0.8 and 0.9 Å for trivalent cations, such that among rare-earth-elements (REE) Dmin/melt is maximum for Lu. Lighter REE become increasingly incompatible with increasing ionic radii. The 12-fold site in Ca-perovskite is larger and has an ideal trivalent site radius of ∼1.05 Å, such that the middle REE has the maximum Dmin/melt. Trivalent cations are generally compatible to highly compatible in Ca-perovskite giving it considerable leverage in crystallization models. Geochemical models based on these phase relations and partitioning results are used to test for evidence in mantle peridotite of preserved signals of crystal differentiation in a deep, Hadean magma ocean.